PENGARUH PEMBERIAN KEFIR SUSU SAPI TERHADAP KADAR KOLESTEROL LDL TIKUS JANTAN SPRAGUE DAWLEY HIPERKOLESTEROLEMIA - Pratama, Sandy Eka; Probosari, Enny (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2012)
Background: Hypercholesterolemia is a main risk factor of cardiovascular disease that remains the higher cause of deaths in the world. Milk kefir contains lactic acid bacteria which can reduce LDL cholesterol. The objective of this study was to determine the effect of milk kefir on LDL cholesterol levels in male Sprague dawley hypercholesterolemia rats. Methods: This research was true-experimental using pre-post test with randomized control group design. Subjects were male Sprague dawley rats, inducted hypercholesterolemia, given milk kefir diet using 1,5 ml, 2 ml, and 3 ml dosage for 15 days. The LDL cholesterol levels were measured by direct method using homogenous enzymatic LDL cholesterol. Normality of the data were tested by Shapiro Wilk test. Data were analyzed by Wilcoxon test and Kruskall-Wallis continued by Mann-Whitney test. Result: The study revealed that milk kefir of dosage 2 ml/day decreased LDL cholesterol significantly (p<0,05) from 196,57 ± 84,11 mg/dl to 38,95 ± 18,22 mg/dl and also for 3 ml/day decreased LDL cholesterol significantly (p<0,05) from 100,14 ± 36,20 mg/dl to 26,91 ± 9,93 mg/dl. Other dosage of 1,5 ml/day is not significantly decrease LDL cholesterol level. Conclusion: Milk kefir able to reduce LDL cholesterol levels in all groups. By giving mik kefir 2 ml/day and 3ml/day during 15 days able to reduce LDL cholesterol levels 80,18% and 73,12%.